A Flight Sensory-Motor to Olfactory Processing Circuit in the Moth Manduca sexta - Bradley, Samual P.; Chapman, Phillip D.; Lizbinski, Kristyn M.; Daly, Kevin C.; Dacks, Andrew M. (Frontiers in Neural Circuits, 2016)
Neural circuits projecting information from motor pathways to sensory pathways are common across sensory domains. These circuits typically modify sensory function as a result of motor pattern activation; this is particularly so in cases where the resultant behavior affects the sensory experience or its processing. However, such circuits have not been observed projecting to an olfactory pathway in any species despite well characterized active sampling behaviors that produce reafferent mechanical stimuli, such as sniffing in mammals and wing beating in the moth Manduca sexta. In this study we characterize a circuit that connects a flight sensory-motor center to an olfactory center in Manduca. This circuit consists of a single pair of histamine immunoreactive (HA-ir) neurons that project from the mesothoracic ganglion to innervate a subset of ventral antennal lobe (AL) glomeruli. Furthermore, within the AL we show that the Manduca sexta histamine B receptor (MsHisClB) is exclusively expressed by a subset of GABAergic and peptidergic LNs, which broadly project to all olfactory glomeruli. Finally, the HA-ir cell pair is present in fifth stage instar larvae; however, the absence of MsHisClB-ir in the larval antennal center (LAC) indicates that the circuit is incomplete prior to metamorphosis and importantly prior to the expression of flight behavior. Although the functional consequences of this circuit remain unknown, these results provide the first detailed description of a circuit that interconnects an olfactory system with motor centers driving flight behaviors including odor-guided flight.